Working Time Regulation, Unequal Lifetimes and Fairness - Marie-Louise Leroux; Gregory Ponthiere (Université du Québec à Montréal, École des sciences de la gestion (ESG UQAM), Département des sciences économiques, 2018)
We examine the redistributive impact of working time regulations in an economy with unequal lifetimes. We first compare the laissez-faire equilibrium with the ex post egalitarian optimum, where the realized lifetime well-being of the worst o (usually the short-lived) is maximized, and show that, unlike the laissez-faire, this social optimum involves an increasing working time age profile and equalizes the realized lifetime well-being of the short-lived and the long-lived. We then examine whether working time regulations can compensate the short-lived. It is shown that uniform working time regulations cannot improve the situation of the short-lived with respect to the laissez-faire, and can only reduce well-being inequalities at the cost of making the short-lived worse o. However, age-specific regulations involving lower working time for the young and higher working time for the old make the short-lived better o, even though such regulations may not fully eradicate well-being inequalities.
Keywords: 330